Kajian Seni Lukis Lekra Dengan Pendekatan Fenomena Estetik - Cholis, Henri (Institut Seni Indoensia Surakarta, 2010)
LEKRA (1950) is a cultural institution established by the PKI. LEKRA brings an artistic concept with the background of party ideology oriented worship Mark, Lenin, and Mao. LEKRA form of art is Socialist Realism, but different with Social Realism that grows in America.Many Indonesian artists who take shelter in LEKRA institutions including: Tarmizi, Affandi, S. Soed-joyono, Henk Ngantung, Hendra Gunawan, Basuki Resobowo, Joko Pekik, also Bumi Tarung studio in Yogyakarta. Situation and political conditions in this country are always changing, bringing art LEKRA find their own fate, in the early turnout revered PKI, which was marginalized in the New Order regime, and now the work of the former painter LEKRA become prey items of art collectors by selling value fantastic and in terms of value of works of art LEKRA a sign of an era of vulgar chaos . Keywords: LEKRA, Art, Ideology. PKI.